Shoppernomics: understanding the structure for marketing communications - Mullin, Roddy (Henry Stewart Talks, 2019)
Shoppernomics, Promotional marketing, Retailing, Customer perspective, Triggers, Engram, Tesco, Tipping point, Subconscious communication, Core market, Early adopters, Social media, Local knowledge, Shopper behaviour